2009
DOI: 10.1152/ajprenal.90660.2008
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin regulation of the renal UT-A3 urea transporter

Abstract: Facilitative urea transporters in the mammalian kidney play a vital role in the urinary concentrating mechanism. The urea transporters located in the renal inner medullary collecting duct, namely UT-A1 and UT-A3, are acutely regulated by the antidiuretic hormone vasopressin. In this study, we investigated the vasopressin regulation of the basolateral urea transporter UT-A3 using an MDCK-mUT-A3 cell line. Within 10 min, vasopressin stimulates urea flux through UT-A3 transporters already present at the plasma me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 31 publications
0
25
1
1
Order By: Relevance
“…AVP is known to regulate the transport function of renal UT-A transporters (7,18,29). In this study, experiments revealed that preincubation for 1 h in 10 Ϫ6 M AVP did not increase DMU-sensitive urea flux in MDCK-bUT-B2 monolayers (NS, n ϭ 3) (see Fig.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…AVP is known to regulate the transport function of renal UT-A transporters (7,18,29). In this study, experiments revealed that preincubation for 1 h in 10 Ϫ6 M AVP did not increase DMU-sensitive urea flux in MDCK-bUT-B2 monolayers (NS, n ϭ 3) (see Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Acute exposure to vasopressin causes a sustained functional increase in both UT-A1 (7) and UT-A3 (27,29), while having a more transient effect on UT-A2 (19). In contrast, for bUT-B2-mediated urea flux, vasopressin had no significant effect (see Fig.…”
Section: Discussionmentioning
confidence: 94%
“…One notable difference between the UT-B and UT-A orthologs is that the latter is upregulated by the antidiuretic hormone vasopressin via phosphorylation of multiple sites on its long cytoplasmic N-terminus (16). Some of this increase in activity can be accounted for by increased localization of UT-A in the plasma membrane (38), but there is also evidence for an increase in urea transport activity that occurs on a more rapid time scale than the rate of accumulation of UT-A in the plasma membrane, possibly due to modulation of UT activity through phosphorylation of proteins already present at the cell surface (39). Given the high conservation of pore-lining residues between UT-B and UT-A, it is tempting to consider the possibility that the S m site barrier is also present in UT-A, but with phosphorylation rather than osmotic stress as the trigger for modulation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, while there appear to be two mechanisms by which LcUT-A3 could be activated, these two actions are not additive in their effects. The intrinsic activation of UT-A3 might be mechanistically related to the mechanism proposed for activation in UT-A3-expressing MDCK cells that involves casein kinase II, protein kinase C, and calmodulin (23). Nevertheless, the consideration that UT-A1 possesses all amino acid residues of UT-A3 (with the exception of its very COOH-terminal residue) and that UT-A1 activation by cAMP is completely abolished by mutating the Lc-residing S486 and S499 to alanines, it would appear that the mechanism(s) that are responsible for activating UT-A3 are of lesser importance for UT-A1 activation.…”
Section: Discussionmentioning
confidence: 98%
“…When heterologously expressed in Madin-Darby canine kidney (MDCK) cells, UT-A1 mediated a urea permeability that was stimulated up to 20-fold over background by vasopressin and forskolin, an activator of adenylate cyclase (6,7). In UT-A3-expressing MDCK cells, basolateral urea influx was enhanced as well (22,23). In cRNA-injected oocytes, UT-A1 and UT-A3 also mediated cAMP-stimulated urea influx (8,21).…”
mentioning
confidence: 99%